2018
DOI: 10.1016/j.arth.2017.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Cup Positioning With the Computed Tomography-Based Two-dimensional to Three-Dimensional Matched Navigation System: A Prospective, Randomized Controlled Study

Abstract: The accuracy of cup positioning in CT-based 2D-3D matched navigation was better than in paired-point matched navigation, and was not affected by patient factors. It is a useful system for even severely deformed pelvises such as developmental dysplasia of the hips.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 34 publications
1
27
0
Order By: Relevance
“…Inadequate orientation of the acetabular component is associated with postoperative impingement [1], dislocation [2], accelerated polyethylene wear [3], liner damage, and restricted range of motion [4]. Surgeons use intraoperative navigation systems to improve the accuracy of implant orientation [5][6][7]. Computed tomography (CT)-based navigation systems that match preoperative images with the actual pelvis use different techniques.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inadequate orientation of the acetabular component is associated with postoperative impingement [1], dislocation [2], accelerated polyethylene wear [3], liner damage, and restricted range of motion [4]. Surgeons use intraoperative navigation systems to improve the accuracy of implant orientation [5][6][7]. Computed tomography (CT)-based navigation systems that match preoperative images with the actual pelvis use different techniques.…”
Section: Introductionmentioning
confidence: 99%
“…2D-3D matching requires radiation exposure because multidirectional fluoroscopic images must be matched with 3D pelvic images reconstructed from preoperative CT data. Paired-point matching navigation is not very accurate in patients with severe deformities [5]. In addition, not all institutions have expensive CT-based navigation systems.…”
Section: Introductionmentioning
confidence: 99%
“…As no differences between robot-assisted and freehand THA were observed in this study, future work may also consider the use of computer navigation systems as these are less costintensive, when compared with robotic arm-assisted THA, and several studies in the literature have demonstrated that computer navigation systems improve component placement. [30][31][32][33] In conclusion, our study suggests that the robot-assisted THA has the potential utility in restoring the native hip geometry with higher accuracy and repeatability than the freehand THA technique. However, as the magnitude of asymmetry in kinematic parameters in all three anatomical planes was comparable between robot-assisted and freehand THA patient groups, this study suggests that, while both robot-assisted and freehand THA have the potential to improve gait symmetry, no differences in gait symmetry at 1-year follow-up existed between both groups.…”
Section: Discussionmentioning
confidence: 62%
“…Lastly, as in vivo kinematics are influenced by multiple factors including patient, implant, and surgical factors, and the sample size for the freehand THA group is small, further study is needed to further elucidate the influences of these parameters on the robotic arm–assisted THA procedure in terms of in vivo kinematics. As no differences between robot‐assisted and freehand THA were observed in this study, future work may also consider the use of computer navigation systems as these are less cost‐intensive, when compared with robotic arm–assisted THA, and several studies in the literature have demonstrated that computer navigation systems improve component placement …”
Section: Discussionmentioning
confidence: 81%
“…However, 3D printing technology cannot reveal the structure of soft tissue, blood vessels, and nerves in a lesion area. Surgical navigation systems and surgical robots provide strong support for the implementation of precision surgery, but the high associated costs, the lack of force feedback, and the tedious training process limit their use.…”
Section: Introductionmentioning
confidence: 99%